Hygienic design of food processing lines to mitigate the risk of bacterial food contamination with respect to environmental concerns. (April 2018) - Faille, Christine; Cunault, Charles; Dubois, Thomas; Bénézech, Thierry
Abstract: Public authorities, chain stakeholders and consumers are all concerned by microbial food safety. Microbiological hazards are one of the most common causes of food poisoning that has been considered for many years but still on the track nowadays considering the recent foodborne disease outbreaks largely reported by the media. Microbial contamination origins are diverse from the field to the plate e.g. soil, air, equipment surfaces, packaging material and staff. Firstly, this article highlights the ways in which the choice of materials plays a major role in surface hygiene. Hydrodynamic conditions directly linked to the equipment geometry are focused on, as is the role played by surfaces in contact with air in surface drying. Surface environmental conditions during processing or cleaning are discussed and new proposals described. Better knowledge of surface contamination and cleaning mechanisms would positively impact hygienic design principles, thereby mitigating any environmental impact of the cleaning operations in the food and beverage industries: new strategies are therefore proposed. Industrial relevance: Hygienic design of food processing equipment is nowadays considered to be mandatory in the reduction of the risk microbial food contamination. The presentation of potential roles of materials on the remaining bacterial soil, after soiling and cleaning, provide new insights when envisaging any hygienic improvements. Equipment design plays a major role in contamination trapping or in the ease of removal via the flow arrangements, notably during cleaning and rinsing operations. More detailed knowledge of the flow mechanical actions combined with the unavoidable chemical action of the detergents would allow industries to go further in enhancing certain "good" phenomena, such as pulsed flow conditions. Last but not least are those possibilities offered by a hygienically designed processing line, in the quest for environmental impact mitigation of cleaning operations i.e. drinking water and energy reductions, or the use of new "green" mild detergents. Highlights: Promising novel approaches to improve hygiene of equipment surfaces cleaned in place Mitigation of environmental impacts of cleaning operations Major role of drying phenomena in the resistance to cleaning of adherent bacteria